2018
DOI: 10.1021/acs.jpcc.8b07002
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Mechanisms of Reversible Dehydrogenation of Formate on N-Doped Graphene-Supported Pd Nanoparticles

Abstract: Reversible formate (HCOO–) dehydrogenation and bicarbonate (HCO3 –) hydrogenation would be desirable for the utilization and storage of hydrogen (H2) as an effective energy carrier. Carbon-supported Pd-based nanoparticles demonstrated enormous competitive advantages for these reactions. However, the fundamental mechanisms underlying these reversible reactions have not yet been elucidated. Herein, we report the reaction pathways for reversible reactions on a Pd-based catalyst using density functional theory (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…644 Another study has also shown that the metal support interaction can be used to shift the d-band center of Pd in N-doped carbon, the smallest d-band center resulting in the lowest energy barrier for formic acid dehydrogenation. 645 Electro-deficient metal NP were also demonstrated to be superior in the case of dehydrogenation of ammonia borane on Pt/CNT catalysts. 646 It was proposed that on oxidized CNT (large amount of oxygen surface group) the charge transfer occurs from the CNT to Pt, whereas on defective CNT (defects and small amount of oxygen surface group), the charge transfer occurs from the Pt to the support.…”
Section: Ag8/n-gmentioning
confidence: 99%
“…644 Another study has also shown that the metal support interaction can be used to shift the d-band center of Pd in N-doped carbon, the smallest d-band center resulting in the lowest energy barrier for formic acid dehydrogenation. 645 Electro-deficient metal NP were also demonstrated to be superior in the case of dehydrogenation of ammonia borane on Pt/CNT catalysts. 646 It was proposed that on oxidized CNT (large amount of oxygen surface group) the charge transfer occurs from the CNT to Pt, whereas on defective CNT (defects and small amount of oxygen surface group), the charge transfer occurs from the Pt to the support.…”
Section: Ag8/n-gmentioning
confidence: 99%
“…Yoon and co-workers reported density functional theory (DFT)-based mechanistic details of these reversible reactions on a Pd-based catalyst and proposed the key points for improving the efficiency of the reaction. [99] Figure 20 shows the mechanism of reversible dehydrogenation and hydrogenation of HCOO À on Ndoped graphene supported Pd nanocatalyst. The DFT modeling is aimed at identifying the factors responsible for efficiency of the reaction.…”
Section: Mechanistic Investigation Of Reversible Formate-bicarbonate mentioning
confidence: 99%
“…Blue and red arrows represent HCOO À dehydrogenation and HCO 3 À hydrogenation, respectively. Reproduced with permission from Ref [99]…”
mentioning
confidence: 99%
“…These changes could take place on the same time scale as the growth of the particles and be closely connected. In such case, there might be significant electronic effects, which affect the binding energy between catalyst, reactants, and products, and inhibit facile product release [43].…”
Section: Co + H 2 O ⇋ Co 2 + Hmentioning
confidence: 99%